Integrating Malay Cultural Practices into Mathematics Learning: Ethnomathematical Approaches Across Indonesia and Malaysia - Ramadhani Ramadhani; Hizmi Wardani; Yugi Diraga Prawiyata; Norzieha Mustapha; Norarida Norarida; Rafiki Ihsan; Alfira Alfira (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study is grounded in the premise that mathematical ideas are inseparable from cultural practices and that ethnomathematics can strengthen the relevance of school mathematics for learners in multicultural contexts. It addresses the persistent gap between students’ everyday cultural experiences and formal mathematics instruction in Indonesia and Malaysia, where mathematics is frequently presented as culturally neutral and decontextualized. The study aims to explore how Malay cultural heritage can be systematically integrated into mathematics learning and to identify culturally situated mathematical concepts that may support students’ conceptual understanding. Employing a qualitative ethnographic design, the researchers collected data through semi- structured interviews with teachers, students, and community members, participatory classroom observations, document analysis of instructional materials, and the examination of cultural artefacts. Data were transcribed and analyzed thematically through iterative reduction, categorization, and interpretive comparison across sites. The findings indicate that Malay architectural artefacts provide rich mathematical representations, particularly geometric forms and measurement-related concepts. Specifically, Maimoon Palace and Istana Jahar exhibit recurring structures such as rectangles, triangles, circles, semicircles, hexagons, octagons, and rhombuses, which align directly with curricular topics including perimeter, area, and volume. Overall, the study concludes that integrating Malay cultural artefacts into mathematics instruction offers a pedagogically robust and culturally responsive approach, with implications for enhancing engagement, supporting conceptual learning, and reinforcing cultural appreciation in the context of globalization